Enhanced Retention, Drainage, and Strength of Old Corrugated Container Pulp Using Poly(aluminum chloride), Nanofibrillated Cellulose, and Hydrophobic Colloidal Silica Particles - Seyed Ali Askarabadi; Mohammad Talaeipour; Hossein Jalali Tarshizi; Amirhooman Hemmasi (BioResources)
The performance of the poly(aluminum chloride) (PAC)-nanofibrillated cellulose (NFC)-colloidal silica (SiO2) system was evaluated relative to the retention and drainage of old corrugated container (OCC) pulp. In this study, OCC pulp was refined to a freeness of 370 ± 10 mL CSF, then different amounts of NFC (0.2, 0.4, and 0.6%) and SiO2 (0.3, 0.6, and 0.9%) in combination with 1% PAC (constant for all treatments) were added. Finally, from these treatments, standard handsheets were made and their physical and mechanical properties were measured according to TAPPI standards. The results showed that the addition of SiO2 and NFC in combination with 1% of PAC each separately and independently increased the burst index, tensile index, and Concora medium test (CMT), but the ring crush test (RCT) decreased. The use of different treatments containing PAC, NFC, and SiO2 also decreased the pulp drainage time and increased their first-pass retention. Also, the use of this system resulted in less water absorption than the control treatment. The use of PAC and NFC in improving the quantitative and qualitative characteristics of OCC fibers can lead to higher first-pass retention, better physical and mechanical properties, while reducing the drainage time.